EFEKTIVITAS DIGITAL ACTIVISM DALAM MEMBANGUN KESADARAN ATAS KEJAHATAN KEKERASAN SEKSUAL BERDASARKAN PRESPEKTIF SOCIOLOGICAL JURISPRUDENCE - Putra, Ariqh Erviana; Senjaya, Oci (Jurnal Ilmiah Wahana Pendidikan, 2024)
The growth of social media in Indonesia creates a lot of spectrum that helps to grow the society’s awareness for a lot of things. Thus, include the realization of how massive sexual harassment has evolved and happened while the law enforcement and the law itself still not ready to handle those phenomenon. This paper will analyze on how social media as a tools for digital activism that helps to indicate the problems and spreads the awareness to Indonesia society about the current situation of sexual harassment in Indonesia and how much progress that the society takes to eradicate this type of crime. This paper will include the data from news site , new media and social media. The method used is the normative juridical research method is a method of literature legal research by conducting it through research primary research materials are laws, government regulations and secondary materials, namely journals, books and websites